Representation and Processing of L2 Compositional Multiword Sequences: Effects of Token Frequency, Type Frequency, and Constituency - Yingying Xu; Yang Yu (Behavioral Sciences)
The present study investigates the effects of token frequency, type frequency, and constituency on L2 compositional multiword sequence (CMS) processing among 60 Chinese L2 English speakers at two proficiency levels, using an online phrasal decision task. The findings reveal the following: (1) Both proficiency groups exhibited a significant token frequency effect in their L2 phrasal and non-phrasal CMS processing, indicating that both sequence types hold psychological reality in L2 learners’ mental representations. (2) The type frequency effect was observed in the higher-proficiency groups’ processing of phrasal and non-phrasal CMSs with low token frequencies, yet it was more pronounced in the less proficient group’s processing of phrasal and non-phrasal CMSs with high token frequencies, indicating that the effect of type frequency operates on a gradient continuum rather than being strictly categorical. (3) Constituency emerged as a robust predictor of processing efficiency, with phrasal CMSs being processed more efficiently than their non-phrasal counterparts across nearly all frequency conditions and proficiency levels. This consistent advantage for phrasal structures underscores the fundamental role of structural integrity in L2 CMS processing. These findings contribute novel insights into the mechanisms underlying L2 CMS processing, while also offering practical pedagogical implications for enhancing L2 CMS acquisition.